BRIDGING ANTICOAGULATION IN PATIENTS WHO REQUIRE TEMPORARY INTERRUPTION OF WARFARIN THERAPY FOR AN ELECTIVE INVASIVE PROCEDURE OR SURGERY (Неотложная медицинская помощь)
Douketis J.D., Spyropoulos A.C., Kaatz S., et al. Perioperative Bridging Anticoagulation in Patients with Atrial Fibrillation // N. Engl. J. Med. – 2015. Jun 22. [Epub ahead of print]